MODEL KINETIKA PENGERINGAN, KADAR SARI DAN KADAR ABU SIMPLISIA TIMI (Thymus vulgaris L.) DENGAN BEBERAPA METODE PENGERINGAN - Devi Safrina; Prambayu Brenda Herera; Eko Supriyanto (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Thyme (Thymus vulgaris L.) is one type of medicinal plant that has been widely used in industry. Utilization of thyme as mostly in the form of dry or commonly known as simplicia. The quality of simplicia (including extractive and ash value) cannot be separated from the drying method used. In addition to the drying method, it is also necessary to know the drying time so that the quality of the water content that meets the requirements is obtained. One way that can be done is to find out the drying kinetic models of the drying method. This study aims to determine the drying kinetic models so that it can be determined prediction of water content during the drying process and its effect on the levels of extractive and ash value simplicia of thyme. Research conducted using 5 drying methods, including drying combination of sunlight and oven cabinet 42oC (P1), combination of sunlight and oven room 40oC (P2), oven room 40oC (P3), oven cabinet 42oC (P4), and sunlight drying (P5) with 3 replications. The results showed that the drying method with oven cabinet produced the highest drying rate approach to the drying kinetic models which was more appropriate for presenting thyme drying, namely the Page method yielded the equation MR = exp (-3.0719t) 0.1314. The drying method has no significant effect on the extractive value and ash value.